2022
DOI: 10.5946/ce.2021.197
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic internal drainage with double pigtail stents for upper gastrointestinal anastomotic leaks: suitable for all cases?

Abstract: Background/Aims: Surgeons and endoscopists have started to use endoscopically inserted double pigtail stents (DPTs) in the management of upper gastrointestinal (UGI) leaks, including UGI anastomotic leaks. We investigated our own experiences in this patient population. Methods: From March 2017 to June 2020, 12 patients had endoscopic internal drainage of a radiologically proven anastomotic leak after UGI surgery in two tertiary UGI centers. The primary outcome measure was the time to removal of the DPTs after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(46 reference statements)
0
5
0
Order By: Relevance
“… 11 In their case series, Toh et al reported successful closure of anastomotic defects using EID in 9 of 12 patients with upper GI fistulas. 12 However, we were not able to find any reports published in the literature where the EID method was used in the closure of an oropharyngeal defect as in our case. To the best of our knowledge, this is the first reported case of repair of an oropharyngeal fistula using the EID technique.…”
Section: Discussionmentioning
confidence: 60%
“… 11 In their case series, Toh et al reported successful closure of anastomotic defects using EID in 9 of 12 patients with upper GI fistulas. 12 However, we were not able to find any reports published in the literature where the EID method was used in the closure of an oropharyngeal defect as in our case. To the best of our knowledge, this is the first reported case of repair of an oropharyngeal fistula using the EID technique.…”
Section: Discussionmentioning
confidence: 60%
“…One advantage of EID is that it enables early enteral feeding. In a retrospective analysis conducted on patients who had a double pigtail tube inserted for internal drainage of an anastomotic leak after upper GI surgery in 2 tertiary upper GI centers, the findings revealed that majority of patients were permitted oral fluids within 1 week and a soft diet in the second week [ 27 ]. Providing early nutritional support and effectively managing sepsis through drainage are crucial components of treatment of anastomotic leakage.…”
Section: Endoscopic Internal Drainage (Eid)mentioning
confidence: 99%
“…Providing early nutritional support and effectively managing sepsis through drainage are crucial components of treatment of anastomotic leakage. Endoscopic internal drainage can improve patient mobility and potentially shorten hospital stay, reducing the risk of complications, such as deep vein thrombosis and hospital-acquired pneumonia that can result from extended hospitalization [ 27 ]. The incidence of adverse events associated with EID typically falls within the range of 4%–15%, with most cases amenable to conservative management.…”
Section: Endoscopic Internal Drainage (Eid)mentioning
confidence: 99%
“…The mean treatment duration for EID was 78.4 days [40]. EID is generally better tolerated than CSEMS and allows for the early resumption of an oral diet [41,42]. EID also does not expose patients to the risks associated with reoperation or percutaneous drainage (i.e., gastrocutaneous fistula) [43].…”
Section: Endoscopic Internal Drainage With Transgastric Double-pigtai...mentioning
confidence: 99%